2022
DOI: 10.1021/acsami.2c03110
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Encapsulation Materials with High Dynamic Water Resistivity and Tissue-Matching Elasticity

Abstract: Flexible implantable medical devices (IMDs) are an emerging technology that may substantially improve the disease treatment efficacy and quality of life of patients. While many advancements have been achieved in IMDs, the constantly straining application conditions impose extra requirements for the packaging material, which needs to retain both high stretchability and high water resistivity under dynamic strains in a physiological environment. This work reports a polyisobutylene (PIB) blendbased elastomer that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, behaviors such as chewing and grinding when eating solid food may wear down the encapsulation layer of the system, leading to acid corrosion, electrical shorts, and even battery leakage. Better biocompatibility may be achieved by introducing adaptively deformable encapsulations, such as cellular microstructures [ 42 ], microfluidic suspensions [ 43 ], and tissue-like materials [ 44 , 45 ] to minimize package degradation. Thereafter, the mean values of the corresponding parameters during sleep and wakefulness were calculated ( Figure 5(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…However, behaviors such as chewing and grinding when eating solid food may wear down the encapsulation layer of the system, leading to acid corrosion, electrical shorts, and even battery leakage. Better biocompatibility may be achieved by introducing adaptively deformable encapsulations, such as cellular microstructures [ 42 ], microfluidic suspensions [ 43 ], and tissue-like materials [ 44 , 45 ] to minimize package degradation. Thereafter, the mean values of the corresponding parameters during sleep and wakefulness were calculated ( Figure 5(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…181 As a result, less free space is available for small molecules to transfer through the film. Butyl rubbers have been applied to protect stretchable organic electronic materials, 182,183 triboelectric nanogenerators, 184 alternating current electroluminescence devices 185 and iongels. 186 However, few of the aforementioned strategies have been applied to printed stretchable electronics.…”
Section: Instability Of Stretchable Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 179 ] Copyright 2022, ACS. f) The image of Ti6Al4V based encapsulation with optical window (top) and SEM image of titanium–glass interface (bottom).…”
Section: Materials For Membrane and Encapsulationmentioning
confidence: 99%
“…Shao et al reported a polyisobutylene blend-based elastomer with high stretchability and high water resistivity, which could potentially be used for packing materials of implantable electrodes (Figure 5e). [179] However, the permeability of many elastomers is higher in comparison with metal and/or non-stretchable polymers, and the issue could be solved by increasing the thickness of the elastomer layer. [180] Natural materials, such as collagen, are conventional materials as the membrane for the implantable electrode.…”
Section: Polymersmentioning
confidence: 99%
See 1 more Smart Citation